Efecto del tiempo de almacenamiento sobre las características fisicoquímicas, antioxidantes y antiproliferativa de néctar de agraz (Vaccinium meridionale Swartz) (2016)
ABSTRACT: Agraz (Vaccinium meridionale Swartz) is a berry that has high antioxidant capacity due to its content of polyphenolic compounds as anthocyanins, phenolic acids and flavonoids. The aim of this study was to evaluate the initial proximal composition and the effect on the physicochemical characteristics (pH, ° Brix, titratable and acidity (TA), antioxidant and antiproliferative activity of nectars made from unripe lyophilized and stored for 42 days. Two nectars were prepared: NA (sucrose) and NB (aspartame), was evaluated change in pH, °Brix and AT every 7 days during storage. It was determined and total phenols content by Folin-Ciocalteu anthocyanins and pH differential method, respectively, antioxidant activity by FRAP and ORAC.Antiproliferative activity with sulforhodamine B in SW480 cells (colon adenocarcinoma) were analyzed. The results showed that both were stable nectars ° Brix, pH and changes in AT. The NB has lower calories. The content of total phenols increased during storage. The anthocyanin content and antioxidant capacity was significantly reduced (p <0.05). NA presented better antiproliferative activity at 72 h, with a percentage of inhibition of cell growth at a concentration of 1g / ml of 63.50% (IC50 = 0.6 g/mL). It can be concluded that NA had a higher antiproliferative capacity and NB better antioxidant activity than even decreased significantly during storage, remained high compared to studies reported in the literature. Further studies "in vivo" to verify their chemopreventive efficacy and elucidate molecular mechanisms of action for the benefit of human health, showing their functional potential described so far "in vitro" are required.